Kehandalan Struktur Anjungan Lepas Pantai Terpancang Empat Kaki di Perairan Natuna - Hermanto, Mochammad Fathurridho; Nandalianadhira, Nafisa (Rekayasa, 2022)
The design of offshore platforms in Indonesia generally uses Working Stress Design (WSD) method rather than Load and Resistance Factor Design (LRFD) method. Whereas the LRFD method produces designs that better describe real conditions with load and capacity factors. The load and capacity factors are obtained from consideration of the uncertainty or randomness of their values. One of the load factors used is the environmental load factor. The environmental load factor of LRFD method is obtained based on environmental characteristics not in Indonesian waters. There are differences in the environmental characteristics of each water. Uncertainty of environmental loads in the offshore platforms design is wave height, current velocities, and wind speed. To get a structure designed according to the characteristics of the waters in Indonesia, an environmental load factor is needed in accordance with the characteristics of Indonesian water. To achieve that, structural reliability analysis is needed. Structures reliabilty represents the possibility of the structure's performance criteria being met which is expressed by the reliability index. The reliability index of structures designed using the WSD method used as a reference for LRFD method. In this study, reliability analysis was carried out using the reserve strength ratio value from the pushover analysis on WSD method. The reliability index of the structure model is 4.10. This value is categorized as high reliability. This results can be used as a reference to determine the environmental load factor of Indonesian water in the future.